Transborder Industrialization in the Framework of Singapore's Regionalization Strategy: The Case of Singapore's Gambit in Vietnam - YEOH, Caroline (Institutional Knowledge at Singapore Management University, 2007)
Infrastructure can be unreliable and administration subject to corruption in Asia’s rapidly emerging economies. This context presented Singapore with unique opportunities to export its expertise to locations where these attributes are less certain, through the provision of superior infrastructure, the ability to negotiate investment concessions and, where existing, through the links to influential business groups in the investment location. This strategic initiative is further premised on the perception that Singapore’s positive reputation with multinationals, as well as ‘guanxi’, or connections, with Asian business networks, will give the industrial-township projects a marketing advantage. Their progress is a litmus test of Singapore’s ability to export its efficiency in industrial park development and management outside its borders. To complement our studies on Singapore’s flagship projects in Indonesia, China and India, this paper takes a closer look at Singapore’s lesser-known project, the Vietnam-Singapore Industrial Park. Evidence from on-site interviews and surveys are presented. This paper concludes that progress in this privileged investment zone remains stymied by particular dependencies in the host environment and, ten years on, the initial optimism with which this project was unveiled has not been justified.